Morphological and Biochemical Variability among Six Popular Varieties of Wheat - Dwivedi, Vikas; Biswas, S. K. (International Journal of Bio-resource and Stress Management, 2011)
Six popular varieties of wheat namely; K-68, K 8207, K 9107, K 9162, PBW 443 and HUW 234 revealed that all these varieties possess variability in terms of morphology and biochemical parameters. Wheat variety K-68 is tall with medium tillering whereas, K 9107 is semi dwarf with synchronous tillering in habit. The potentiality of grain yield also differed amongst the varieties, showing a maximum of 54q ha-1 in K 9107 against 27q ha-1 in the variety K 8027. The test weight and crop duration also varied widely. Biochemical analysis of the wheat varieties revealed that among the six wheat varieties, the maximum soluble protein (41.86 mg g-1 of fresh leaf) was observed in the variety K 9107, which was followed by K 8027 (39.23 mg g-1 of fresh leaf) whereas, HUW 234 exhibited lowest value of 32.54 mg g-1 of fresh leaves. Similarly, total phenol content was also found maximum in the variety K 9107 (3.92 mg g-1 of fresh leaf) against a maximum of 3.24 mg g-1 of fresh leaf in HUW 234. SDS-PAGE profiling of soluble protein revealed that the number of bands present in each variety ranged from 06 to 12, indicating variability among the six wheat varieties in this respect. Similarly, crude protein, total nitrogen and fat per cent in wheat flour also showed variation among the varieties.